Compositionally graded SS316 to C300 Maraging steel using additive manufacturing. (March 2021) - Ben-Artzy, A.; Reichardt, A.; Borgonia, J.-P.; Dillon, R.P.; McEnerney, B.; Shapiro, A.A.; Hosemann, P.
Abstract: Joining of dissimilar metals is required for numerous applications in industries such as chemical, energy and automotive. It is challenging due to differences in melting point, density, and thermal expansion of the metals being joined. Common welding techniques involve limiting melting and solidification to a narrow area leading to high thermal stresses and potentially brittle intermetallic phases. Furthermore, the geometric complexity of these welded joints can be rather limited. Additive Manufacturing (AM) presents new techniques for joining of dissimilar metals. One of the emerging methods is the building of functionally graded parts using Directed Energy Deposition (DED) to spatially vary composition. In this paper, a SS316 L and C300 maraging steel couple were joined by DED and heat treated. 13 discrete composition layers were selected using metallurgical considerations, in order to ensure a smooth transition in properties and microstructure. The mechanical properties of the as-built joints were found to be similar to the SS part and no intermetallic phases were found in the interface. Graphical abstract: Unlabelled Image Highlights: Graded direct energy deposition additive manufacturing between 316L-C300 Continues change of fcc and bcc volume fraction along the graded lengthF Sudden change of mechanical properties at a specific layer rather than a graded property transition.